The Influence of a Child-Friendly Learning Environment on the Emotional Development Early Childhood Childern at PAUD RA Al Marzuqiyah Ciracas Jak-tim - Herminastiti, Rini (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of a child-friendly learning environment on early childhood emotional development at PAUD RA Al Marzuqiyah Ciracas, East Jakarta. A child- friendly learning environment includes five main dimensions: physical safety, emotional support from educators, child participation, inclusiveness, and a positive social environment. This study used a quantitative approach with multiple linear regression method, involving 48 children aged 4-6 years. The research instrument was a Likert scale-based questionnaire filled out by classroom teachers. The results of the analysis showed that a child-friendly learning environment simultaneously had a significant effect on children's emotional development, with a coefficient of determination (R²) of 0.651. Partially, the three sub-variables that have a significant effect are emotional support from educators, child participation, and positive social environment. The emotional support subvariable from teachers had the most dominant influence on children's emotional development, such as the ability to recognize and express feelings, empathy, and self-regulation. Meanwhile, the other two sub-variables-physical safety and formal inclusiveness-did not show a statistically significant effect. This suggests that physical aspects and inclusion policies need to be more actively integrated into social-emotional learning practices. The conclusion of this study emphasizes the importance of affective teacher-child relationships and participatory learning in creating environments that support children's emotional health from an early age.